2014
DOI: 10.1111/cge.12337
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum and prevalence of BRCA1 and BRCA2 genes in patients with familial and early‐onset breast/ovarian cancer from Tunisia

Abstract: The contribution of BRCA1/BRCA2 mutations to hereditary breast cancer in the Tunisian population has not been accurately estimated. The purpose of our study was to estimate the incidence and spectrum of pathogenic mutations in BRCA1/2 genes in early onset and familial breast/ovarian cancer among Tunisian women. To identify predictive factors for BRCA1/2 mutations, we screened the entire coding sequences and intron/exon boundaries of BRCA1/BRCA2 genes in 48 patients by direct sequencing. Twelve pathogenic mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 22 publications
6
55
0
Order By: Relevance
“…This finding is in line with a Korean study conducted across 36-centers (22.3%) (17). The mutation rate appears generally lower compared to Western countries (23~35.3%) (18)(19)(20)(21)(22), but higher compared to Peking or Shanghai regions (10.5~18.2%) (23)(24)(25). Lower prevalence of BRCA mutation is in line with comparisons of BC incidence with the Western countries.…”
Section: Discussionsupporting
confidence: 87%
“…This finding is in line with a Korean study conducted across 36-centers (22.3%) (17). The mutation rate appears generally lower compared to Western countries (23~35.3%) (18)(19)(20)(21)(22), but higher compared to Peking or Shanghai regions (10.5~18.2%) (23)(24)(25). Lower prevalence of BRCA mutation is in line with comparisons of BC incidence with the Western countries.…”
Section: Discussionsupporting
confidence: 87%
“…However, data from our previous study reported a higher frequency of UVs, about 37% (Riahi et al 2013). Therefore, in our population, the characterization of the impact of such variants is of great importance.…”
Section: Introductionmentioning
confidence: 77%
“…In order to provide more accurate assessment of the breast cancer risk, the characterization of the functional impact of UVs is a decisive step especially for populations with high rates of UVs as the Tunisian one where UVs account for 37% of all identified BRCA variations (Riahi et al 2013). In this case, non-informative results can be a source of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings between differing repeat lengths showed that shorter CAG repeats may play protective roles against breast cancer, as opposed to longer repeat lengths, which may contribute to cancer development (Gottlieb et al, 2013). The study demonstrates that merely identifying genetic variations does not provide sufficient understanding of cancer etiology; rather it is necessary to determine frequency and distribution of mutations between cancerous and normal tissues (Gottlieb et al, 2013; Riahi et al, 2014). …”
Section: Discoveriesmentioning
confidence: 99%